Endothelial cell‐secreted MIF reduces pericyte contractility and enhances neutrophil extravasation. Issue 2 (25th September 2018) - Pellowe, Amanda S.; Sauler, Maor; Hou, Yue; Merola, Jonathan; Liu, Rebecca; Calderon, Brenda; Lauridsen, Holly M.; Harris, Mariah R.; Leng, Lin; Zhang, Yi; Tilstam, Pathricia V.; Pober, Jordan S.; et al.
ABSTRACT: Dysregulated neutrophil extravasation contributes to the pathogenesis of many inflammatory disorders. Pericytes (PCs) have been implicated in the regulation of neutrophil transmigration, and previous work demonstrates that endothelial cell (EC)‐derived signals reduce PC barrier function; however, the signaling mechanisms are unknown. Here, we demonstrate a novel role for EC‐derived macrophage migration inhibitory factor (MIF) in inhibiting PC contractility and facilitating neutrophil transmigration. With the use of micro‐ELISAs, RNA sequencing, quantitative PCR, and flow cytometry, we found that ECs secrete MIF, and PCs upregulate CD74 in response to TNF‐α. We demonstrate that EC‐derived MIF decreases PC contractility on 2‐dimensional silicone substrates via reduction of phosphorylated myosin light chain. With the use of an in vitro microvascular model of the human EC–PC barrier, we demonstrate that MIF decreases the PC barrier to human neutrophil transmigration by increasing intercellular PC gap formation. For the first time, an EC‐specific MIF knockout mouse was used to investigate the effects of selective deletion of EC MIF. In a model of acute lung injury, selective deletion of EC MIF decreases neutrophil infiltration to the bronchoalveolar lavage and tissue and simultaneously decreases PC relaxation by increasing myosin light‐chain phosphorylation. We conclude that paracrine signals from EC via MIF decrease PC contraction and enhance PC‐regulated neutrophil transmigration.—Pellowe, A. S., Sauler, M., Hou, Y., Merola, J., Liu, R., Calderon, B., Lauridsen, H. M., Harris, M. R., Leng, L., Zhang, Y., Tilstam, P. V., Pober, J. S., Bucala, R., Lee, P. J., Gonzalez, A. L. Endothelial cell‐secreted MIF reduces pericyte contractility and enhances neutrophil extravasation. FASEB J. 33, 2171–2186 (2019). www.fasebj.org